2014
DOI: 10.1017/s0047404514000372
|View full text |Cite
|
Sign up to set email alerts
|

The social motivations of reversal: Raisedboughtin New York City English

Abstract: This article presents a variationist analysis of theboughtvowel in New York City English (NYCE) and finds that it has reversed the trajectory of change outlined in Labov (1966). An acoustic analysis of production data from sixty-four native residents of the Lower East Side demonstrates thatboughtis lowering in apparent time, a change led by young people, white and Jewish speakers, and the middle classes. A second source of data comes from perceptions of raisedboughtgathered from a matched guise experiment, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…Specifically, we saw that increased PFPTL is associated with a particular kind of exaggerated affect in perception, and if we follow the work noted earlier that draws on perceptual social meanings to explain production patterns (Becker, 2014;Chappell, 2016), we might say that the social differences in PFPTL production are driven by differences in affective expression: women and gay men employ more PFPTL to express more exaggerated affect (i.e., flamboyance and emotiveness), and straight men employ less PFPTL to express an affect that is more reserved. The precise and nuanced relations among gender and sexual categories, and affect and expressivity, cannot be commented on in-depth for this sample of speakers due to a lack of ethnographic observation.…”
Section: Affect and Social Differencesupporting
confidence: 58%
“…Specifically, we saw that increased PFPTL is associated with a particular kind of exaggerated affect in perception, and if we follow the work noted earlier that draws on perceptual social meanings to explain production patterns (Becker, 2014;Chappell, 2016), we might say that the social differences in PFPTL production are driven by differences in affective expression: women and gay men employ more PFPTL to express more exaggerated affect (i.e., flamboyance and emotiveness), and straight men employ less PFPTL to express an affect that is more reserved. The precise and nuanced relations among gender and sexual categories, and affect and expressivity, cannot be commented on in-depth for this sample of speakers due to a lack of ethnographic observation.…”
Section: Affect and Social Differencesupporting
confidence: 58%
“…As Eckert (2008) and other Third Wave linguists noted, sociolinguistic variables occupy an “indexical field” of meanings, with different meanings becoming salient depending on context. (oh) in NYC is no exception: as Becker (2014) showed, listeners associate raised variants with a “classic New Yorker” persona who is also “mean and aloof.” To the extent that these less positive meanings have also been internalized by speakers, the relationships among place, stance, and usage posited here may be obscured.…”
Section: Discussionmentioning
confidence: 99%
“…While it is tempting to assume that place‐linked features necessarily index place itself, these data support the view that “localized” features can take on additional social meanings via orders of indexicality (Eckert, 2008; Johnstone et al, 2006; Silverstein, 2003). Movement away from these features can therefore be driven in part by opposition to the social meanings or personae with which they have become linked, rather than opposition to the location itself (Becker, 2014). Additionally, we suggest that similar directional changes in various locales can be driven by different social motivators.…”
Section: Discussionmentioning
confidence: 99%
“…In Northeastern cities, studies have revealed movement away from localized linguistic features over time, such as Philadelphia’s complex “short‐a” system (e.g. Labov, Rosenfelder, & Fruehwald, 2013) and THOUGHT‐raising in New York City (Becker, 2014). Most recently, stagnation or reversal of the long‐progressing Northern Cities Vowel Shift (NCS), the well‐studied vocalic system characteristic of the US Inland North (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation